Influence Of Ultrasonic Waves on The Activity of Above and Nadp - Dependent Liver Isocytedehydrogenase in Rats and Ways of Their Correction - Mukhamedov, Gafurdjon; Babakhanova, Dilnoza; Mirkhamidova, Parida; Alimova, Rano; Shakhmurova, Gulnara; Eshonkulov, Otabek (Journal of Neonatal Surgery, 2025)
Isocitrate dehydrogenase is a key enzyme in the tyrcarboxylic acid cycle and is involved in the oxidative decarboxylation of isocitrate (IC) to form alpha-ketoglutarate (α-ketoglutarate) and CO2. The goal was to investigate the effect of ultrasonic waves on the activity of lipid peroxidation, isocitrate dehydrogenase in rat liver mitochondria, as well as the effect of mulberry leaf extract and biosep oil extract. The experiment involved white lab rats weighing 180-200 grams each. The ultrasound device used was Mindrey DP-50 Vet. The work is based on the following methods: Schneider differential centrifugation, spectrophotometry, chromatography, pH-metry, photometry. The article presents data on the suppression of the activity of NAD and NADP-dependent isocitrate dehydrogenase (IDH) enzymes in liver mitochondria in rats irradiated with ultrasound for 5 minutes. Deep inhibition of enzymes was observed on the 1st and 3rd days after exposure to ultrasonic waves (ultrasound), which in turn led to disruption of membrane structures and changes in lipid peroxidation processes in rat liver mitochondria. In the groups of rats, in which the correction was carried out with mulberry extract and biosep oil extract, restoration of the activity of NAD and NADP-IDH enzymes in liver mitochondria was observed. The obtained data show that the correction effects of mulberry extract were more effective than those of biosep oil extract